Hepatocyte ploidy in cats with and without hepatocellular carcinoma. - Post, Jacqueline.; Langohr, Ingeborg M.; Webster, Cynthia R.L.; Mottram, Peter.; Liu, Chin-Chi.; Johnston, Andrea. (Tufts University. Tisch Library., 2021)
Keywords: Ploidy, Liver, Hepatocellular carcinoma, Feline.; Springer Open.